Annealing method of sulfur oxide scintillation ceramic

By using a sulfur source to generate sulfur vapor under vacuum atmosphere, the sulfur oxide scintillation ceramics are annealed, which solves the problems of sulfur vacancies defects in high-temperature vacuum annealing and oxidation in air annealing, which improves the light output performance and mechanical strength of the ceramics and enhances the yield rate.

CN119707527APending Publication Date: 2025-03-28FIRST MATERIALS CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411938363.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-26
Publication Date
2025-03-28

AI Technical Summary

Technical Problem

Sulfur oxide scintillation ceramics are prone to sulfur vacancy defects during high-temperature vacuum annealing, and are easily oxidized when annealed in the air, resulting in a reduced scintillation performance. During the annealing process, the ceramics are prone to local overheating and stress concentration, reducing the yield rate of production.

Method used

The method of annealing under vacuum atmosphere is adopted to place the sulfur oxide scintillation ceramics into the crucible, mix the ceramic powder with the sulfur source to form filler, and landfill the ceramics in the crucible, and generate sulfur vapor at high temperature through the sulfur source to create a sulfur-containing atmosphere, protect the surface of the ceramic and eliminate sulfur vacancy.

Benefits of technology

Effectively eliminate sulfur vacancy in ceramics, improve light output performance, reduce thermal stress, improve mechanical strength and yield, avoid oxidation reactions, and improve crystal structure and crystallinity.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119707527A_ABST
    Figure CN119707527A_ABST
Patent Text Reader

Abstract

The invention belongs to the field of an annealing process of oxysulfide ceramics, and discloses an annealing method of oxysulfide scintillation ceramics. Comprising the following steps: (1) putting sulfur oxide scintillation ceramic into a crucible; ceramic powder and a sulfur source are mixed to form a filler, the filler is used for filling the sulfur oxide scintillation ceramic in the crucible, and the ceramic powder and the sulfur oxide scintillation ceramic have the same components; and (2) placing the crucible in a heating furnace, starting an annealing program, and annealing the sulfur oxide scintillation ceramic in a vacuum atmosphere. According to the annealing method, the light output, the production yield, the crystallinity and the uniformity of the crystal size of the sulfur oxide scintillation ceramic can be improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of sulfide oxide ceramic annealing technology, in particular to an annealing method for sulfide oxide scintillating ceramics. Background Art

[0002] Rare earth ion doped oxysulfide scintillating ceramics (such as gadolinium oxysulfide scintillating ceramics) have the advantages of high density, high light yield, stable chemical properties, relatively simple preparation process, and no cleavage during processing. They have become ideal scintillator materials with excellent comprehensive performance for radiation inspection instruments or detectors such as X-CT, high-speed X-ray scanners and article security inspectors.

[0003] The preparation process of sulfur oxide scintillating ceramics is complicated, and the impurity phase is difficult to control; oxygen / sulfur vacancy defects are easily generated during powder calcination or high-temperature sintering of ceramics, resulting in reduced scintillation performance such as light output and afterglow. Therefore, annealing of ceramics is very necessary. Annealing treatment will have the following problems: (1) Currently, the most commonly used annealing methods are vacuum annealing, air annealing, inert atmosphere or weak reducing atmosphere annealing. However, since the S in the structure of oxysulfide scintillating ceramics is unstable, annealing in a high-temperature vacuum environment can easily make the sulfur vacancy defects more serious. In addition, oxysulfide scintillating ceramics are easily oxidized at high temperatures and are not suitable for long-term annealing in air.

[0004] (2) Local overheating of the ceramic during the annealing process will cause stress concentration inside the material, which will lead to cracks and reduce the production yield of oxysulfide scintillating ceramics.

[0005] (3) When annealing is performed in an air atmosphere, the ceramic may react with oxygen to produce oxide impurities (such as gadolinium oxide), which will affect the performance of the ceramic. Summary of the invention

[0006] The object of the present invention is to provide an annealing method for oxysulfide scintillating ceramics to solve at least one technical problem existing in the background technology.

[0007] To achieve the above purpose, the technical solution adopted by the present invention is: A method for annealing oxysulfide scintillating ceramics comprises the following steps: (1) placing sulfur oxide scintillation ceramics into a crucible; mixing ceramic powder and a sulfur source to form a filler, and using the filler to fill the sulfur oxide scintillation ceramics in the crucible, wherein the ceramic powder and the sulfur oxide scintillation ceramics have the same components; (2) The crucible is placed in a heating furnace, and the annealing program is started to anneal the sulfur oxide scintillating ceramic in a vacuum atmosphere.

[0008] Furthermore, the sulfur oxide in the sulfur oxide scintillation ceramic is RE 2 O2 S, RE is at least one of Gd, Tb, Y, La, Eu, Nd, Ce, Er, and Pr.

[0009] Furthermore, the mass ratio of the ceramic powder to the sulfur source in the filler is 20~1:1.

[0010] Furthermore, the sulfur source is a sulfur-containing compound that can generate sulfur vapor or sulfur-containing gas by heating; during the annealing process, the sulfur source is heated in a heating furnace to generate sulfur vapor or sulfur-containing gas, and the sulfur vapor or sulfur-containing gas contacts the sulfur oxide scintillating ceramic. By controlling the heating temperature and time of the sulfur source, the generation rate and amount of sulfur vapor can be effectively controlled, thereby controlling the sulfur pressure.

[0011] Preferably, the sulfur-containing compound includes but is not limited to sublimated sulfur, sulfur, sulfate, bisulfite, sulfite, sodium thiosulfate, and the like.

[0012] It is further preferred that the sulfur source is sublimated sulfur, and the purity of the sublimated sulfur is not less than 98%.

[0013] Furthermore, the oxidized sulfide scintillating ceramic to be annealed is subjected to a polishing pre-treatment, preferably using a polishing machine to grind and polish the oxidized sulfide scintillating ceramic on both sides to a mirror surface, so as to remove impurities on the surface of the oxidized sulfide scintillating ceramic.

[0014] Furthermore, the ceramic powder and the sulfur source are mixed and ground to form a filler.

[0015] Furthermore, after landfilling, the outer surface of the oxysulfide scintillating ceramic is covered with fillers.

[0016] Further preferably, the thickness of the filler between the sulfur oxide scintillating ceramic and the bottom of the crucible is 1-5 cm; the thickness of the filler between the sulfur oxide scintillating ceramic and the side wall of the crucible is 1-5 cm; the thickness of the filler covering the sulfur oxide scintillating ceramic is 1-10 cm.

[0017] Furthermore, the annealing temperature is 800°C to 1200°C.

[0018] Further preferably, the annealing procedure is: at a heating rate of β 1 Temperature rise, 0<β 1 ≤20℃ / min, until the furnace temperature reaches T 1 , 600≤T 1 ≤800℃, with heating rate β 2 Temperature rise, 0<β 2 ≤20℃ / min, until the furnace temperature reaches T 2 , 800≤T 2 ≤1200℃, constant temperature 2~12h, where β 1 >β2 , T 1 <T 2 .

[0019] More preferably, 3≤β 1 ≤15℃ / min; 1≤β 2 ≤10℃ / min; constant temperature for 2~8h.

[0020] Further, after the constant temperature is finished, the temperature is lowered at a rate V 1 Cooling, 0<V 1 <20℃ / min, until the furnace temperature drops to 600~800℃, at a cooling rate V 2 Cool down, 5≤V 2 ≤20℃ / min, until the furnace temperature drops to 200~500℃, terminate the program, where V 1 <V 2 ; More preferably, 3≤V 1 ≤10℃ / min; 5≤V 2 ≤15℃ / min.

[0021] Furthermore, after annealing is completed, the filler is recovered and can be recycled.

[0022] Furthermore, after annealing, the annealed oxysulfide scintillating ceramic is washed with deionized water and then wiped with dilute nitric acid to remove surface impurities. It is further preferred that the concentration of the dilute nitric acid used does not exceed 10wt%, and it is further preferred that the concentration of the dilute nitric acid is 3-5wt%.

[0023] Compared with the prior art, the present invention has the following beneficial effects: The present invention grinds and mixes the ceramic powder used in the oxysulfide scintillating ceramic with a sulfur source to form a uniform mixture, and uses the mixture as a filler to protect the surface of the oxysulfide scintillating ceramic to be annealed while generating a required sulfur-containing gas environment, thereby effectively eliminating sulfur vacancies in the ceramic and improving the light output performance of the crystal.

[0024] The present invention buries and covers the sulfide scintillating ceramics that need to be annealed with fillers, thereby avoiding the thermal stress generated by the direct contact between the surface of the sulfide scintillating ceramics being annealed and the crucible during the annealing process, creating a more uniform annealing environment, and being more conducive to the release of thermal stress, so that the ceramics have higher mechanical strength and avoid cracking during cutting and array processing. Therefore, the yield rate of the sulfide scintillating ceramics annealing processing using this annealing method is greatly improved compared with the traditional annealing method.

[0025] The present invention grinds and polishes the oxysulfide scintillating ceramics and removes impurities on the surface of the oxysulfide scintillating ceramics before annealing, which can improve the transmittance of the oxysulfide scintillating ceramics to a certain extent and further improve the yield rate of the oxysulfide scintillating ceramics produced by the present invention.

[0026] The present invention places a sulfur source in a vacuum sealing device, which can reduce the oxidation reaction between ceramics and oxygen, help improve the crystal structure and grain growth of the ceramics, and at high temperatures, the migration and recrystallization process of the ceramic crystals are smoother, which is beneficial to the growth of ceramic grains and the rearrangement of grain boundaries, and improves the crystallinity of the ceramics and the uniformity of the crystal size.

[0027] The present invention performs annealing under vacuum sealing conditions, uses a sulfur source to evaporate under high temperature to become sulfur vapor to create a sulfur-containing atmosphere condition, and after the annealing is completed, the sulfur vapor condenses, and there is no need to carry out tail gas treatment, and there is no waste gas pollution. BRIEF DESCRIPTION OF THE DRAWINGS

[0028] The accompanying drawings are used to provide further understanding of the present invention and constitute a part of the specification. They are used to explain the present invention together with the embodiments of the present invention and do not constitute a limitation of the present invention.

[0029] In the attached picture: Figure 1 It is a schematic diagram of the annealing device of the present invention.

[0030] Figure 2 This is a flow chart of the annealing process of the present invention.

[0031] Figure 3 This is a comparison chart of the relative light output test of the annealed ceramics of Example 1 and Comparative Example 1.

[0032] Figure 4 This is the XRD spectrum of the ceramic after annealing in Example 2. DETAILED DESCRIPTION

[0033] In order to facilitate the understanding of the present invention, the present invention will be described more comprehensively and carefully below in conjunction with the accompanying drawings and preferred embodiments, but the protection scope of the present invention is not limited to the following specific embodiments.

[0034] Unless otherwise defined, all the professional terms used below have the same meanings as those generally understood by those skilled in the art. The professional terms used herein are only for the purpose of describing specific embodiments and are not intended to limit the scope of protection of the present invention.

[0035] Unless otherwise specified, various raw materials, reagents, instruments and equipment used in the present invention can be purchased from the market or prepared by existing methods.

[0036] Example 1 A method for annealing oxysulfide scintillating ceramics, such as Figure 2 As shown, the following steps are included: (1) Use a polishing machine to perform double-sided grinding and polishing on the gadolinium oxysulfide scintillation ceramic to remove impurities on the surface of the gadolinium oxysulfide scintillation ceramic.

[0037] Take ceramic powder with the same composition as gadolinium oxysulfide scintillating ceramic, take sublimated sulfur with a purity of 99% as a sulfur source, grind the ceramic powder and the sulfur source in a mortar at a mass ratio of 5:1, and evenly mix the powder to obtain a filler.

[0038] (2) If Figure 1 As shown, the filler is evenly spread on the bottom of the corundum crucible, and then the gadolinium oxysulfide scintillation ceramic to be annealed is placed, and the filler is evenly scattered around the gadolinium oxysulfide scintillation ceramic to be annealed until the filler completely wraps the gadolinium oxysulfide scintillation ceramic to be annealed, thereby preventing the gadolinium oxysulfide scintillation ceramic from directly contacting the inside of the crucible. The thickness of the filler between the gadolinium oxysulfide scintillation ceramic and the bottom of the crucible is 1.5 cm, the thickness of the filler between the gadolinium oxysulfide scintillation ceramic and the inner wall of the crucible is 1.5 cm, and the thickness of the filler covering the gadolinium oxysulfide scintillation ceramic is 3 cm.

[0039] (3) Place the corundum crucible in a high-temperature corundum tube furnace, and then evacuate the furnace chamber until the vacuum indication is -0.1 MPa. Then set the program for annealing. First, heat it at 10°C / min. When the temperature of the gadolinium oxysulfide scintillating ceramic reaches 800°C, reduce the heating rate to 5°C / min until the temperature of the tube furnace chamber reaches 900°C.

[0040] (4) After being kept at a constant temperature of 900°C for 4 hours, the temperature is lowered at a rate of 5°C / min. When the temperature of the gadolinium oxysulfide scintillating ceramic reaches 800°C, the cooling rate is increased to 10°C / min. The program is terminated after the temperature drops to 300°C. After the temperature naturally drops to room temperature, the annealed gadolinium oxysulfide scintillating ceramic is taken out and the filler is collected for reuse next time. The annealing is then completed.

[0041] (5) After the annealed ceramic is washed with deionized water, it is wiped with 5 wt% dilute nitric acid to remove surface impurities.

[0042] Example 2 A method for annealing oxysulfide scintillating ceramics, such as Figure 2 As shown, the following steps are included: (1) Use a polishing machine to perform double-sided grinding and polishing on the gadolinium oxysulfide scintillation ceramic to remove impurities on the surface of the gadolinium oxysulfide scintillation ceramic.

[0043] Take ceramic powder with the same composition as gadolinium oxysulfide scintillating ceramic, take sublimated sulfur with a purity of 99% as a sulfur source, grind the ceramic powder and the sulfur source in a mortar at a mass ratio of 10:1, and evenly mix the powder to obtain a filler.

[0044] (2) If Figure 1 As shown, the filler is evenly spread on the bottom of the corundum crucible, and then the gadolinium oxysulfide scintillation ceramic to be annealed is placed, and the filler is evenly sprinkled around the gadolinium oxysulfide scintillation ceramic to be annealed until the filler completely wraps the gadolinium oxysulfide scintillation ceramic to be annealed, thereby preventing the gadolinium oxysulfide scintillation ceramic from directly contacting the inside of the crucible. The thickness of the filler between the gadolinium oxysulfide scintillation ceramic and the bottom of the crucible is 2 cm, the thickness of the filler between the gadolinium oxysulfide scintillation ceramic and the inner wall of the crucible is 2 cm, and the thickness of the filler covering the gadolinium oxysulfide scintillation ceramic is 4 cm.

[0045] (3) Place the corundum crucible in a high-temperature corundum tube furnace, and then evacuate the furnace chamber until the vacuum indication is -0.1 MPa. Then set the program for annealing. First, heat it at 10°C / min. When the temperature of the gadolinium oxysulfide scintillating ceramic reaches 800°C, reduce the heating rate to 5°C / min until the temperature of the tube furnace chamber reaches 1000°C.

[0046] (4) After being kept at a constant temperature of 1000°C for 4 hours, the temperature is lowered at a rate of 5°C / min. When the temperature of the gadolinium oxysulfide scintillating ceramic reaches 800°C, the cooling rate is increased to 15°C / min. The program is terminated after the temperature drops to 300°C. After the temperature naturally drops to room temperature, the annealed gadolinium oxysulfide scintillating ceramic is taken out and the filler is collected for reuse next time. The annealing is then completed.

[0047] (5) After the annealed ceramic is washed with deionized water, it is wiped with 5 wt% dilute nitric acid to remove surface impurities.

[0048] Example 3 A method for annealing oxysulfide scintillating ceramics, such as Figure 2 As shown, the following steps are included: (1) Use a polishing machine to perform double-sided grinding and polishing on the gadolinium oxysulfide scintillation ceramic to remove impurities on the surface of the gadolinium oxysulfide scintillation ceramic.

[0049] Take ceramic powder with the same composition as gadolinium oxysulfide scintillating ceramic, take sublimated sulfur with a purity of 99.9% as a sulfur source, grind the ceramic powder and the sulfur source in a mortar at a mass ratio of 10:1, and evenly mix the powder to obtain a filler.

[0050] (2) If Figure 1As shown, the filler is evenly spread on the bottom of the corundum crucible, and then the gadolinium oxysulfide scintillation ceramic to be annealed is placed, and the filler is evenly scattered around the gadolinium oxysulfide scintillation ceramic to be annealed until the filler completely wraps the gadolinium oxysulfide scintillation ceramic to be annealed, thereby preventing the gadolinium oxysulfide scintillation ceramic from directly contacting the inside of the crucible. The thickness of the filler between the gadolinium oxysulfide scintillation ceramic and the bottom of the crucible is 1.5 cm, the thickness of the filler between the gadolinium oxysulfide scintillation ceramic and the inner wall of the crucible is 1.5 cm, and the thickness of the filler covering the gadolinium oxysulfide scintillation ceramic is 3 cm.

[0051] (3) Place the corundum crucible in a high-temperature corundum tube furnace, and then evacuate the furnace chamber until the vacuum indication is -0.1 MPa. Then set the program for annealing. First, heat it at 10°C / min. When the temperature of the gadolinium oxysulfide scintillating ceramic reaches 800°C, reduce the heating rate to 5°C / min until the temperature of the tube furnace chamber reaches 1100°C.

[0052] (4) After being kept at a constant temperature of 1100°C for 4 hours, the temperature is lowered at a rate of 5°C / min. When the temperature of the gadolinium oxysulfide scintillating ceramic reaches 800°C, the cooling rate is increased to 10°C / min. The program is terminated after the temperature drops to 300°C. After the temperature naturally drops to room temperature, the annealed gadolinium oxysulfide scintillating ceramic is taken out and the filler is collected for reuse next time. The annealing is then completed.

[0053] (5) After the annealed ceramic is washed with deionized water, it is wiped with 5 wt% dilute nitric acid to remove surface impurities.

[0054] Example 4 A method for annealing oxysulfide scintillating ceramics, such as Figure 2 As shown, the following steps are included: (1) Use a polishing machine to perform double-sided grinding and polishing on the gadolinium oxysulfide scintillation ceramic to remove impurities on the surface of the gadolinium oxysulfide scintillation ceramic.

[0055] Take ceramic powder with the same composition as gadolinium oxysulfide scintillating ceramic, take sublimated sulfur with a purity of 99.9% as a sulfur source, grind the ceramic powder and the sulfur source in a mortar at a mass ratio of 10:1, and evenly mix the powder to obtain a filler.

[0056] (2) If Figure 1As shown, the filler is evenly spread on the bottom of the corundum crucible, and then the gadolinium oxysulfide scintillation ceramic to be annealed is placed, and the filler is evenly scattered around the gadolinium oxysulfide scintillation ceramic to be annealed until the filler completely wraps the gadolinium oxysulfide scintillation ceramic to be annealed, thereby preventing the gadolinium oxysulfide scintillation ceramic from directly contacting the inside of the crucible. The thickness of the filler between the gadolinium oxysulfide scintillation ceramic and the bottom of the crucible is 1.5 cm, the thickness of the filler between the gadolinium oxysulfide scintillation ceramic and the inner wall of the crucible is 1.5 cm, and the thickness of the filler covering the gadolinium oxysulfide scintillation ceramic is 3 cm.

[0057] (3) Place the corundum crucible in a high-temperature corundum tube furnace, and then evacuate the furnace chamber until the vacuum indication is -0.1 MPa. Then set the program for annealing. First, heat it at 10°C / min. When the temperature of the gadolinium oxysulfide scintillating ceramic reaches 800°C, reduce the heating rate to 5°C / min until the temperature of the tube furnace chamber reaches 1000°C.

[0058] (4) After being kept at a constant temperature of 1000°C for 6 hours, the temperature is lowered at a rate of 5°C / min. When the temperature of the gadolinium oxysulfide scintillating ceramic reaches 800°C, the cooling rate is increased to 10°C / min. The program is terminated after the temperature drops to 300°C. After the program is terminated and the temperature is naturally lowered to room temperature, the annealed gadolinium oxysulfide scintillating ceramic is taken out and the filler is collected for reuse next time. The annealing is then completed.

[0059] (5) After the annealed ceramic is washed with deionized water, it is wiped with 5 wt% dilute nitric acid to remove surface impurities.

[0060] Example 5 A method for annealing oxysulfide scintillating ceramics, such as Figure 2 As shown, the following steps are included: (1) Use a polishing machine to perform double-sided grinding and polishing on the gadolinium oxysulfide scintillation ceramic to remove impurities on the surface of the gadolinium oxysulfide scintillation ceramic.

[0061] Take ceramic powder with the same composition as gadolinium oxysulfide scintillating ceramic, take sublimated sulfur with a purity of 99.9% as a sulfur source, grind the ceramic powder and the sulfur source in a mortar at a mass ratio of 20:1, and evenly mix the powder to obtain a filler.

[0062] (2) If Figure 1As shown, the filler is evenly spread on the bottom of the corundum crucible, and then the gadolinium oxysulfide scintillation ceramic to be annealed is placed, and the filler is evenly scattered around the gadolinium oxysulfide scintillation ceramic to be annealed until the filler completely wraps the gadolinium oxysulfide scintillation ceramic to be annealed, thereby preventing the gadolinium oxysulfide scintillation ceramic from directly contacting the inside of the crucible. The thickness of the filler between the gadolinium oxysulfide scintillation ceramic and the bottom of the crucible is 1.5 cm, the thickness of the filler between the gadolinium oxysulfide scintillation ceramic and the inner wall of the crucible is 1.5 cm, and the thickness of the filler covering the gadolinium oxysulfide scintillation ceramic is 3 cm.

[0063] (3) Place the corundum crucible in a high-temperature corundum tube furnace, and then evacuate the furnace chamber until the vacuum indication is -0.1 MPa. Then set the program for annealing. First, heat it at 10°C / min. When the temperature of the gadolinium oxysulfide scintillating ceramic reaches 600°C, reduce the heating rate to 5°C / min until the temperature of the tube furnace chamber reaches 800°C.

[0064] (4) After being kept at a constant temperature of 800°C for 4 hours, the temperature is lowered at a rate of 10°C / min. When the temperature of the gadolinium oxysulfide scintillating ceramic reaches 400°C, the program is terminated. After naturally cooling to room temperature, the annealed gadolinium oxysulfide scintillating ceramic is taken out and the filler is collected for reuse next time. The annealing is then completed.

[0065] (5) After the annealed ceramic is washed with deionized water, it is wiped with 5 wt% dilute nitric acid to remove surface impurities.

[0066] Comparative Example 1 An annealing method for oxysulfide scintillating pottery comprises the following steps: (1) Use a polishing machine to perform double-sided grinding and polishing on the gadolinium oxysulfide scintillation ceramic to remove impurities on the surface of the gadolinium oxysulfide scintillation ceramic.

[0067] (2) Place the gadolinium oxysulfide scintillation ceramic to be annealed into a corundum crucible.

[0068] (3) Place the corundum crucible in a high-temperature corundum tube furnace. After adding insulation bricks at both ends of the corundum tube, anneal it directly in an air atmosphere. First, heat it up at a rate of 10°C / min. When the temperature of the gadolinium oxysulfide scintillating ceramic reaches 600°C, reduce the heating rate to 5°C / min until the temperature of the tube furnace cavity reaches 800°C.

[0069] (4) After being kept at a constant temperature of 800°C for 4 hours, the temperature is lowered at a rate of 10°C / min. When the temperature of the gadolinium oxysulfide scintillating ceramic reaches 400°C, the program is terminated. After naturally cooling to room temperature, the annealed gadolinium oxysulfide scintillating ceramic is taken out and the filler is collected for reuse next time. The annealing is then completed.

[0070] (5) After the annealed ceramic is washed with deionized water, it is wiped with 5 wt% dilute nitric acid to remove surface impurities.

[0071] The relative light output of the annealed ceramics of Example 1 and Comparative Example 1 was tested using the scintillation performance testing platform SPM_Platform, with a NA22 source and a testing time of 180s. The test results are shown in Figure 3 As shown, it can be seen that the effect of improving the light output of the gadolinium oxysulfide scintillating ceramic by annealing in a sulfur-containing atmosphere in Example 1 is significantly better than that by annealing in air.

[0072] Figure 4 This is the XRD spectrum of the ceramic after annealing in Example 2. It can be seen from the figure that its diffraction peak is sharp, the crystallinity is good, the position of the diffraction peak is completely consistent with the standard card, and there is no impurity phase.

[0073] The above are only preferred embodiments of the present invention and are not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the scope of the present invention.

Claims

1. A method for annealing oxysulfide scintillating ceramics, characterized in that: The following steps are involved: (1) placing sulfur oxide scintillation ceramics into a crucible; mixing ceramic powder and a sulfur source to form a filler, and using the filler to fill the sulfur oxide scintillation ceramics in the crucible, wherein the ceramic powder and the sulfur oxide scintillation ceramics have the same components; (2) The crucible is placed in a heating furnace, and the annealing program is started to anneal the sulfur oxide scintillating ceramic in a vacuum atmosphere.

2. The annealing method according to claim 1, characterized in that The oxysulfide in the oxysulfide scintillating ceramic is RE2O2S, and RE is at least one of Gd, Tb, Y, La, Lu, Eu, Nd, Ce, Er, Pr, Yb, and Sm.

3. The annealing method according to claim 1, characterized in that The mass ratio of the ceramic powder to the sulfur source in the filler is 20-1:

1.

4. The annealing method according to claim 1, characterized in that The sulfur source is a sulfur-containing compound that can generate sulfur vapor by heating; Preferably, the sulfur source is at least one of sublimated sulfur, sulfur, sulfate, bisulfite, sulfite, and sodium thiosulfate; Preferably, the sulfur source is sublimated sulfur, and the purity of the sublimated sulfur is not less than 98%.

5. The annealing method according to claim 1, characterized in that: The ceramic powder and the sulfur source are mixed and ground to form a filler.

6. The annealing method according to claim 1, characterized in that: After landfilling, the outer surfaces of the oxysulfide scintillating ceramics are all covered with fillers.

7. The annealing method according to claim 6, characterized in that: The thickness of the filler between the sulfur oxide scintillation ceramic and the bottom of the crucible is 1-5 cm; the thickness of the filler between the sulfur oxide scintillation ceramic and the side wall of the crucible is 1-5 cm; the thickness of the filler covering the sulfur oxide scintillation ceramic is 1-10 cm.

8. The annealing method according to claim 1, characterized in that: The annealing temperature is 800℃~1200℃.

9. The annealing method according to claim 8, characterized in that: The annealing procedure is: heating at a heating rate β1, 0<β1≤20℃ / min, until the furnace chamber temperature reaches T1, 600≤T1≤800℃, heating at a heating rate β2, 0<β2≤20℃ / min, until the furnace chamber temperature reaches T2, 800≤T2≤1200℃, and keeping the temperature constant for 2~12h, wherein β1>β2, T1<T2; Preferably, 3≤β1≤15℃ / min; 1≤β2≤10℃ / min; constant temperature for 2~8h.

10. The annealing method according to claim 8 or 9, characterized in that: After the constant temperature is finished, the temperature is lowered at a cooling rate V1, 0<V1<20℃ / min, until the furnace chamber temperature drops to 600~800℃, and the temperature is lowered at a cooling rate V2, 5≤V2≤20℃ / min, until the furnace chamber temperature drops to 200~500℃, and the program is terminated, wherein V1<V2; Preferably, 3≤V1≤10℃ / min; 5≤V2≤15℃ / min.